EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING DIPADU THINK PAIR SHARE TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR MAHASISWA - rizkiwati, baiq yuliana; Jailani, Huzain (Educatio, 2015)
This research is aimed to analyze the Effectiveness model of learning Problem Based Learning combined Think Pair Share of critical thinking Skills and Learning Outcomes student. The subjects of the research are class A as the experimental class and class B as the control class. e research subjects are taken with random sampling technique soon after the class homogeneity is accounted. The research design of this thesis is quasi experiment with essay test as the research instrument. The analysis technique used in this research is t-test with the assist from SPSS 16.0 for Windows.The research shows that there is a significant influence exhibited in the average score of the experimental class and control class both in critical and creative thinking abilities. Based on the t-test result on the creative thinking ability, the significance level of critical thinking ability on p-level is 0,011 and the significance level of creative thinking ability on p-level is 0,00. Both p-level data are lower than the significance level 0,05 (p<0,05). Therefore, we can draw the conclusion that the PBL and TPS model has certain influence on the critical and creative thinking ability. Student response to the enforceability of PBL learning model TPS on the material combined employment and unemployment as a whole is positive. Similarly, the response of the lecturer for combined PBL learning model TPS is considered quite appropriate when applied to the subject. Keywords: Problem Based Learning combined Think Pair Share, Critical Thinking Skills, Learning Results.